Identifying Psychological and Sociological Factors Affecting Job Aspirations in Lower Secondary Students - Farid Ahmadi; Soheila Ahmadi (جامعه شناسی کاربردی)
Introduction Quaglia and Cobb define a student’s aspiration as the ability to establish future goals and to be motivated in the present to pursue them (Quaglia & Cobb, 1996, p. 130). Job aspiration specifically refers to an individual's desire for future employment (Powell & Butterfield, 2003). In Iran, students are expected to formulate career goals during the first cycle of high school, marking a critical period for job-related decision-making. The choices students make regarding their academic fields of study and career paths are essential components of effective career guidance. Having clear job aspirations before entering the second cycle of high school significantly influences students’ professional lives and future success. To understand these aspirations fully, educators must recognize the factors that shape them to intervene effectively (Herbert, 1989). Additionally, it is crucial for governments and policymakers to grasp students’ job and educational aspirations in order to design strategic programs that promote educational and economic success. Consequently, our study aimed to investigate job aspirations, psychological and social predictors, and perceived reasons for job choice among lower secondary students in Iran.